Methotrexate-associated lymphoproliferative disorders: management by watchful waiting and observation of early lymphocyte recovery after methotrexate withdrawal. Issue 11 (2nd November 2015) - Inui, Yumiko; Matsuoka, Hiroshi; Yakushijin, Kimikazu; Okamura, Atsuo; Shimada, Takaki; Yano, Shingo; Takeuchi, Mai; Ito, Mitsuhiro; Murayama, Tohru; Yamamoto, Katsuya; Itoh, Tomoo; Aiba, Keisuke; et al.
Abstract : No optimum treatment of iatrogenic immunodeficiency-associated lymphoproliferative disorders due to methotrexate in patients with rheumatoid arthritis (MTX-LPD) has yet been established, although MTX withdrawal is known to have a substantial effect on tumor regression. Here, we retrospectively analyzed 20 cases of MTX-LPD. Tumor shrinkage occurred in 18 of 20 cases, but only following MTX withdrawal. This tumor regression ratio was considerably better than in previous reports, and appeared due to longer "watchful waiting." Lymphocyte recovery at 2 weeks after MTX withdrawal was significantly higher in cases with tumor regression in 1 month than in those without tumor regression ( p = 0.001). Median time to maximal efficacy after MTX cessation in cases without chemotherapy was 12 weeks (range 2–76). In conclusion, watchful waiting for a longer period after MTX cessation with observation of early lymphocyte recovery and uninterrupted continuation of other anti-rheumatoid drugs may be an acceptable management plan for MTX-LPD.